NEOLOGY OF ARABIC TERMS IN THE COVID-19 PANDEMIC (MORPHOLOGICAL STUDY) - Itsnaini Muslimati Alwi; Nurul Aini (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2021)
This study aims to determine the forms and rules of formation the Covid-19 Pandemic term in Arabic from the morphological aspect. The type of this research is library research, which conducted by reviewing and analyzing library data sources. The data of the research are Arabic terms of COVID-19 taken from Dictionary of Covid-19 Term (English-French-Arabic) which published by Arab League Educational, Cultural, and Scientific Organization (ALECSO). The results of this study indicate the form of Covid-19 Pandemic terms in Arabic which consists of words and phrases. The word form consists of nouns and verbs, both in the form of root words and affixes. The form of the phrase consists of tarkib idhafi, verbal phrases, noun phrases, jar majrur, and tarkib washfi. There are 46 (24%) word form and 146 (76%) phrase form. The process of forming COVID-19 terms in Arabic using several methods, there are: a) Neology by derivation, which consists of: masdar, isim fa'il, isim maf'ūl, isim alat, and Sighat al-Mubalaghah. b) Neology by arabizing foreign vocabulary or absorption, and c) Neology by translating foreign vocabulary into Arabic. Based on the research, there are 25 (52%) masdar words, 5 (10%) isim fa’il words, 2 (4%) isim alat words, 1 (2%) sighat al-mubalaghah word, 2 (4%) isim maf’ul words, 6 (13%) absorption words, 7 (15%) translation words  about COVID-19 term in Arabic.